2017
DOI: 10.1007/s12687-016-0289-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of in silico protein sequence analysis in the clinical classification of variants in cancer risk genes

Abstract: Missense variants represent a significant proportion of variants identified in clinical genetic testing. In the absence of strong clinical or functional evidence, the American College of Medical Genetics recommends that these findings be classified as variants of uncertain significance (VUS). VUSs may be reclassified to better inform patient care when new evidence is available. It is critical that the methods used for reclassification are robust in order to prevent inappropriate medical management strategies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
(46 reference statements)
4
19
1
Order By: Relevance
“…This means, that nsSNPs classified as benign by SIFT or MutationTaster2 are actual benign variants in the overwhelming majority of cases, i.e., false negative predictions are rare. In agreement with our findings, Kerr et al [ 34 ] observed no false negative calls of SIFT in a set of 69 pathogenic BRCA1/2 nsSNPs. However, confirmation of our hypothesis and its application in clinical diagnostics requires further investigation on larger data sets.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This means, that nsSNPs classified as benign by SIFT or MutationTaster2 are actual benign variants in the overwhelming majority of cases, i.e., false negative predictions are rare. In agreement with our findings, Kerr et al [ 34 ] observed no false negative calls of SIFT in a set of 69 pathogenic BRCA1/2 nsSNPs. However, confirmation of our hypothesis and its application in clinical diagnostics requires further investigation on larger data sets.…”
Section: Discussionsupporting
confidence: 93%
“…We refer to Additional file 3 : Table S2 for a summarizing review. The poor results of PolyPhen-2 when compared with Align-GVGD, SIFT and MutationTaster2 in our study are in agreement with a previous study from Rodrigues et al [ 15 ], as well as with the specificities obtained by Hicks et al, Kerr et al, and Miosge et al [ 12 , 34 , 35 ]. However, we were not able to confirm the results of Kerr et al [ 34 ] that indicated a poor performance of SIFT on BRCA1/2 missense variants, especially concerning its specificity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In predicting the effect of missense SNPs on UGT1A1, Rodrigues et al (2015) demonstrated that 13 of the 20 tools had an MCC close to zero, and only the predictor of MutPred reached a value of MCC ≥ 0.7 (Rodrigues et al, 2015). Kerr et al (2017) used 7 tools to predict the functional impact of variants of the BRCA1, BRCA2, MLH1 and MSH2 genes associated with hereditary cancer, and demonstrated that within the evaluated set, 5 algorithms had coefficients below 0.35 and only two tools (Align -GVGD (0.65) and MAPP-MMR (0.59)) had MCCs greater than 0.59 (Kerr et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these algorithms are not highly sensitive in isolation and tend to ‘over predict’ missense changes as pathogenic 27. Thus, there is a need to develop better in silico models that show higher specificity and sensitivity; it may be that models will need to be calibrated on a gene-by-gene basis.…”
Section: There Is a Demand For Functional Assays To Classify Brca1/2 mentioning
confidence: 99%